The Impact of Culture and Personality Traits on Financial Literacy - putra, aswin andika; wijayanti, ra afera ratna (LIAISON JOURNAL OF BEST, 2025)
This research study investigates the influence of culture and personality traits on financial literacy, employing the Hofstede Cultural Dimensions framework and the big five personality traits as theoretical foundations. Specifically, the research aims to analyze the impact of cultural aspects of Indulgence, Long-Term Orientation, and Uncertainty Avoidance, alongside the personality traits of openness and conscientiousness, on various dimensions of financial literacy. Utilizing structural equation modelling analysis, the study reveals that that culture had an insignificant direct impact on individuals' financial literacy, while showing its significant indirect influence through mediating factors, such as personality traits. In contrast, personality traits, exhibited a significant and positive influence on financial literacy. The study underscores the need for a multifaceted approach to enhancing financial education, addressing both direct and indirect factors, which is likely to be more effective in promoting financial literacy among individuals. Keywords: culture, Hofstede Cultural Dimensions, personality traits, financial literacy